2004
DOI: 10.1097/00054725-200403000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recombinant Human Growth Hormone (rhGH) on Trinitrobenzene Sulfonic Acid-induced Colitis in Rats

Abstract: The limited efficacy of standard medical therapies for inflammatory bowel diseases has resulted in a continuing search for alternative treatments. Growth hormone (GH) has shown to have mutagenic and proliferative effects on intestinal cells. This study was designed to identify the effect of growth hormone on trinitrobenzene slfonic acid-induced colitis (TNBSIC) in rats. This study was carried out on 30 rats, divided in 3 groups: group 1: TNBSIC+ GH, group 2: TNBSIC, group 3: saline enema. Colitis was induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…IGF was shown to promote epithelial repair in intestinal inflammation in preclinical animal models. For example, recombinant human growth hormone induced protective effects in TNBS-induced colitis [309]. A preliminary study showed that human growth factor was effective in CD, it improved the clinical symptoms (the number of liquid/soft stools, severity of abdominal pain and overall well being) and a statistically significant increase in circulating levels of IGF-1 was observed [310].…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%
“…IGF was shown to promote epithelial repair in intestinal inflammation in preclinical animal models. For example, recombinant human growth hormone induced protective effects in TNBS-induced colitis [309]. A preliminary study showed that human growth factor was effective in CD, it improved the clinical symptoms (the number of liquid/soft stools, severity of abdominal pain and overall well being) and a statistically significant increase in circulating levels of IGF-1 was observed [310].…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%
“…19 The ability of GH to promote epithelial repair in the setting of gutassociated inflammation has been demonstrated in several animal models. [20][21][22] In 1 such study, colitis was induced with dextran sodium sulfate (DSS) in transgenic mice overexpressing GH. These mice displayed susceptibility to chemical-induced colitis similar to that of the wild-type mice; however, they showed improved survival, less intestinal inflammation, and a marked increase in epithelial repair.…”
Section: Growth Hormone (Hgh)mentioning
confidence: 99%
“…21 Similar protective effects by exogenous administration of GH was also observed in TNBS-induced colitis. 22 Additional studies have also investigated the potential antifibrogenic effect of GH. In 1 study, ileocecal colitis was induced in Lewis rats by injection of peptidoglycan-polysaccharide (pg-aps), with subsequent injection of recombinant human growth hormone (hGH) for 14 days.…”
Section: Growth Hormone (Hgh)mentioning
confidence: 99%
“…Whilst recombinant human growth hormone (rhGH) is a therapeutic possibility in children with IBD who grow slowly, its efficacy remains unclear. Preliminary results from the rat colitis model suggest that linear growth and bone formation rate in rats treated with rhGH and prednisolone are in fact better compared with nontreated colitis rats and those treated with prednisolone alone [48]. There is also a possibility that rhGH treatment may be associated with a beneficial effect on the disease process and, thereby, improve growth [49,50,51].…”
Section: Use Of Other Growth-promoting Therapymentioning
confidence: 99%